What does the Brazilian Unified Health System offer in terms of care technologies for people with Autism Spectrum Disorder? - Saraiva, Emanuela Machado Silva; Tavares, Ana Raquel Bezerra Saraiva; Silva, Vanusa Maria Gomes Napoleão; Santos, Maria Solange Nogueira dos; Maia, Maria Isabel Ribeiro de Andrade; Aragão, Gislei Frota; Chaves, Edna Maria Camelo (Seven Editora, 2023)
Autism spectrum disorder is a neurodevelopmental disorder characterized by impairment in communication and social interaction and behavioral problems, such as repetitive behaviors and restricted patterns of interest. The treatment of people with autism  should be based on the implementation of multidisciplinary strategies that aim to prevent and intervene early in behavioral excesses and deficits through rehabilitation therapies that should be directed according to the needs of each person. Within the scope of  the Unified Health System, the document entitled Line of care for the care of people with autism spectrum disorders and their families in the Psychosocial Care Network of the Unified Health System, lists 07 (seven) technologies aimed at the care of these individuals. It is possible that health professionals will find it difficult to apply the proposed technologies, as well as the availability of these technologies will be limited, requiring the government to develop and implement public policies that guarantee the necessary infrastructure for the best possible care for people with autism spectrum disorder and their families. DOI:https://doi.org/10.56238/sevened2023.004-022